Informing national adaptation for sustainable development through spatial systems modelling. (November 2021) - Fuldauer, Lena I.; Thacker, Scott; Hall, Jim W.
Highlights: A methodology to inform national adaptation in the context of the SDGs is proposed. Hazard impacts are spatially modelled across all a nation's built and natural assets. Results help add spatial granularity and specificity to NDCs and NAPs. The natural environment provides critical adaptation services to the built environment. Policy-making on adaptation must consider multi-hazard and cross-sectoral impacts. Abstract: Acute climate-change hazards, such as floods or storm surges, can affect a nation's built and natural environment assets that are critical for development and achievement of the Sustainable Development Goals (SDGs). To reduce the impacts of such acute climate-change hazards and safeguard development, national decision-makers require evidence on where and how hazards affect SDG achievement to better inform adaptation. Here, we develop a systems methodology that spatially models the impacts of climate-change hazards across a nation's entire built and natural environment assets and its interdependent influences on the SDG targets to inform national adaptation. We apply our methodology in Saint Lucia through a participatory approach with decision-makers across 18 government ministries, academia, and the private sector. Results reveal that acute climate-change hazards can affect half of Saint Lucia's assets across 22 sectors, which can influence 89% of all SDG targets. Application of our methodology provided evidence on where and how to prioritise adaptation, thereby helping to add spatial granularity to 52 measures under Saint Lucia's National Adaptation Plan (NAP) as well as specificity on how limited capacity for cross-sectoral coordination can be directed to safeguard SDG targets. Adaptation does not necessarily imply investing in physical asset protection: results show the need to protect critical natural environments which provide important adaptation services to the built environment. As more nations develop and revise their NAPs and Nationally Determined Contributions under the Paris Agreement, strategic planning across sectors – as demonstrated in Saint Lucia – will be critical to facilitate adaptation that safeguards SDG achievement.